2019
DOI: 10.1007/s42380-019-00040-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of School Climate and Empathy on Cyberbystanders’ Intention to Assist or Defend in Cyberbullying

Abstract: Bystanders play a crucial role in aggressive behavior in group contexts. Cyberbystanders can react in proactive ways such as assisting a cyberbully or defending the victim. Since school relationships spill over to the online world, the school context is likely to influence students' online behavior. In the present study, we examine the influence of school climate on active cyberbystanding behavior beyond the influence of individual social competences. Participants were 726 students from a more comprehensive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…While various demographic factors were addressed, age and gender were the most commonly studied across the articles included in this review and were the only demographic factors identified as being significantly associated with negative cyber-bystander behavior, with some exceptions which provided contradicting results by Schultze-Krumbholz et al ( 40 ), Erreygers et al ( 41 ), and Barlinska et al ( 42 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…While various demographic factors were addressed, age and gender were the most commonly studied across the articles included in this review and were the only demographic factors identified as being significantly associated with negative cyber-bystander behavior, with some exceptions which provided contradicting results by Schultze-Krumbholz et al ( 40 ), Erreygers et al ( 41 ), and Barlinska et al ( 42 ).…”
Section: Resultsmentioning
confidence: 93%
“…Schultze-Krumbholz et al ( 40 ) found that lower levels of positive peer interactions in class was associated with assistant behavior cyber-aggression situations. Additionally, they also stated that classrooms that contained a higher number of offline-aggressors tend to promote more negative cyber-bystander behavior—likely due to social norms and pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Van Cleemput et al (2014) used self-reported measures and determined that bystanders who joined in cyberbullying scored lower on trait empathy. Schultze-Krumbholz et al (2020) used hypothetical scenarios to assess cyberbullying bystander behaviours and found that participants with high trait empathy were less likely to assist in cyberbullying. However, other studies have indicated that trait empathy is unrelated to cyberbullying bystanders' aggressive behaviours.…”
Section: Backgrou N Dmentioning
confidence: 99%
“…Eight studies (Caravita, Gini, & Pozzoli, 2012;Haddock & Jimerson, 2017;Jenkins et al, 2017;Machackova & Pfetsch, 2016;Schultze-Krumbholz, Zagorscak, Hess, & Scheithauer, 2020;Yang & Kim, 2017;Walters & Espelage, 2019) investigated bystander roles, showing a strong relation between defending and affective empathy. Two studies failed to find a relation between defending and cognitive empathy (Caravita et al, 2012;Walters & Espelage, 2019).…”
Section: Disengagementmentioning
confidence: 99%